Slaves and Labor Pools The Combination of Slavery and Work for Hire - Varella, Claudia; Barcia, Manuel (University Press of Florida, 2022)
When slaves were seized, complications often arose between those claiming ownership over them. Dire as their situation was, things took a turn for the worse when coartados entered the depósitos, where their special status as slaves was suspended and, in consequence, they stopped receiving income. Síndicos were charged with helping the coartados in the depósito, and with serving as their legal protectors, but it was not uncommon for the síndicos or their colleagues to try to squeeze some economic benefit out of the relationship.
Keywords: coartados; despositos; slaves; síndicos; legal protectors; WOS(2)